A collaborative agreement for berth allocation under excessive demand. (March 2018) - Dulebenets, Maxim A.; Golias, Mihalis M.; Mishra, Sabya
Abstract: International seaborne trade has increased significantly during the last three decades, and this growth is expected to continue at similar rates. To address the growing demand, terminal operators aim to improve productivity with the minimum capital investment. This study extends an existing berth allocation policy, where demand can be diverted from a multi-user maritime container terminal to an external maritime container terminal at an additional cost. Furthermore, additional market based rules are introduced in the model for the vessel diversion decision making. The objective of the multi-user maritime terminal operator is to minimize the total vessel service cost. Due to complexity of the proposed mathematical formulation, a Memetic Algorithm is developed to solve the resulting problem. A number of numerical experiments are presented to evaluate efficiency of the new berth allocation policy and the solution algorithm. Results indicate that the suggested berth allocation policy yields substantial cost savings during high demand periods. Highlights: A collaborative agreement is proposed for berth allocation where vessels can be diverted from one maritime container terminal to another. Additional market based rules are introduced for the vessel diversion decision making. A mixed integer non-linear mathematical model is formulated for the proposed berth allocation policy. A Memetic Algorithm that applies two groups of local search heuristics is developed to solve the problem. Numerical experiments demonstrate efficiency of the developed algorithm and proposed berth allocation policy.